Impact of social media influencer marketing on customer purchase intention in the fashion industry: a systematic literature review - George, Ajimon; Shibu, Milcah; Joseph, Eric Thomas; Sunny, Prajod (Frontiers in Communication, 2025)
IntroductionResearch on social media influencer marketing has grown significantly in recent decades, particularly in the fashion industry. This field is crucial for marketers, management, and influencers because of its strong influence on customer purchase decisions.MethodsThis systematic literature review employed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework to ensure a transparent and rigorous process for identifying and selecting relevant studies. To analyze and organize the findings, the ADO-TCM framework was applied, enabling a structured examination of antecedents, decisions, and outcomes (ADO), as well as the underlying theories, contexts, and methods (TCM) used in prior research.ResultsThe review highlights credibility, trust, and attractiveness as the most frequently studied antecedents influencing the effectiveness of influencer marketing. Source credibility theory and the theory of planned behavior were identified as the dominant theoretical lenses guiding existing research.DiscussionDespite the growth of scholarship in this area, significant gaps remain, particularly regarding contextual variations, methodological diversity, and emerging digital marketing trend. This study contributes by synthesizing fragmented research, identifying future research opportunities, and offering guidelines for marketers, management, and influencers. These insights aim to enhance the strategic use of influencer marketing and support customers in making informed purchase decisions in the dynamic fashion industry.